Anaerobic energy production during sprint paddling in junior competitive and recreational surfers - Minahan, C. L.; Pirera, D. J.; Sheehan, B.; MacDonald, L.; Bellinger, P. M. (International Journal of Sports Physiology and Performance, 2016)
This study compared determinants of a 30-s all-out paddling effort (30-s sprint-paddling test) between junior surfboard riders (surfers) of varying ability. Eight competitive (COMP) and 8 recreational (REC) junior male surfers performed a 30-s sprint-paddling test for the determination of peak sprint power and accumulated O2 deficit. Surfers also performed an incremental-paddling test for the determination of the O2 uptake-power output relationship that was subsequently used to calculate the accumulated O2 deficit for the 30-s sprint-paddling test. During the 30-s sprint-paddling test, peak sprint power (404 ± 98 vs 292 ± 56 W, respectively, P = .01) and the accumulated O2 deficit (1.60 ± 0.31 vs 1.14 ± 0.38 L, respectively, P = .02) were greater in COMP than in REC surfers, whereas peak O2 uptake measured during the incremental-paddling test was not different (2.7 ± 0.1 vs 2.5 ± 0.2 L/min, respectively, P = .11). The higher peak sprint power and larger accumulated O2 deficit observed in COMP than in REC surfers during a 30-s sprint paddling test suggest that surfing promotes development of the anaerobic energy systems. Furthermore, peak sprint power determined during 30 s of sprint paddling may be considered a sensitive measure of surfing ability or experience in junior male surfers.